2003
DOI: 10.1029/2002jd002744
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurements of particulate elemental carbon on the ground observation network over the western North Pacific during the ACE‐Asia campaign

Abstract: The measurements of atmospheric aerosol and associated species have been carried out on the ground observation network over the western North Pacific as part of the Variability of Marine Aerosol Properties (VMAP) project. The network consists of four Japanese islands (Rishiri, Sado, Hachijo, and Chichi‐jima), ranging widely in latitudes from 25°N to 45°N along with the line of 140°E. In this paper, we report on simultaneous measurements of particulate elemental carbon (EC) on the four islands from March to May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 11 publications
4
28
0
Order By: Relevance
“…The obtained trace metal concentration levels in the aerosol were almost of the same as those obtained previously at Oki Island, Japan (Mukai et al, 1990), 1/10-1/70 of those obtained at Beijing, China (Okuda et al, 2004), and 1/2-1/40 of those obtained at Tokyo, Japan (Mizohata et al, 2000). Moreover, the concentration levels of the obtained watersoluble ionic constituents in the aerosol corresponded almost entirely to previous observation results for Rishiri Island from March to May 2001 (Matsumoto et al, 2003).…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…The obtained trace metal concentration levels in the aerosol were almost of the same as those obtained previously at Oki Island, Japan (Mukai et al, 1990), 1/10-1/70 of those obtained at Beijing, China (Okuda et al, 2004), and 1/2-1/40 of those obtained at Tokyo, Japan (Mizohata et al, 2000). Moreover, the concentration levels of the obtained watersoluble ionic constituents in the aerosol corresponded almost entirely to previous observation results for Rishiri Island from March to May 2001 (Matsumoto et al, 2003).…”
Section: Methodssupporting
confidence: 86%
“…Rishiri is close to Siberia; it is 50 km from Sakhalin and 800 km from Vladivostok, Russia. Previous studies performed on Rishiri Island (Matsumoto et al, 2003) and Okushiri Island, which is located about 370 km southwest of Rishiri Island (Rahn et al, 1989), were focused on sector analysis of the inflow of air pollutants from Russia, China, and the Japanese mainland. Based on the previous studies, we classified the area surrounding Rishiri Island geographically into four sectors "Marine", "Japan", "China", and "Siberia" for our sector analysis (Figure 3).…”
Section: The Features Of the Chemical Constituents In Tsp For Each Aimentioning
confidence: 99%
“…The amounts of carbonaceous substances evolved at 280 and 340 • C were defined as organic carbon (OC) and 750 • C as total carbon (TC), and the difference between the two is the EC. Detailed description of this instrument has been given in the previous studies [31,[34][35][36]. Meanwhile R&P 5400 has a high resolution of 0.25 g m −3 and it was calibrated by Beijing Branch of Rupprecht & Patashnick Co. Inc. before it was deployed.…”
Section: Continuous Observation Of Organic and Element Concentrationsmentioning
confidence: 99%
“…3(d), 3(e), and 5). On the basis of simultaneous observations at remote sites, Matsumoto et al (2003) reported that the transport patterns of polluted air masses moving from East Asia to the northern Northwest Pacific are often different from those moving to the southern Northwest Pacific. In addition, the number of low-and high-pressure systems moving eastward from South China increases in spring (Uno et al, 2000;Hatakeyama et al, 2001;Shimada et al, 2011).…”
Section: Contribution To Ec (%)mentioning
confidence: 99%